+0  
 
0
287
1
avatar

Log4(x+2)+log4(x-2=2

Guest Jun 15, 2017
 #1
avatar+27047 
+1

I assume you want to find x

 

\(\log_4(x+2)+\log_4(x-2)= 2\\ \log_4((x+2)(x-2))=2 \\ (x+2)(x-2)=4^2\\x^2-4=16 \\ x^2= 20 \\ x=\pm2\sqrt5\)

However, the negative value is not valid in the original equation, so \(x = 2\sqrt5\)

Alan  Jun 15, 2017

9 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.